Nuclear RNA Decay Pathways Aid Rapid Remodeling of Gene Expression in Yeast - Bresson, Stefan (Mol Cell, 2017)
In budding yeast, the nuclear RNA surveillance system is active on all pre-mRNA transcripts and modulated by nutrient availability. To test the role of nuclear surveillance in reprogramming gene expression, we identified transcriptome-wide binding sites for RNA polymerase II and the exosome cofactors Mtr4 (TRAMP complex) and Nab3 (NNS complex) by UV crosslinking immediately following glucose withdrawal (0, 4, and 8 min). In glucose, mRNA binding by Nab3 and Mtr4 was mainly restricted to promoter-proximal sites, reflecting early transcription termination. Following glucose withdrawal, many growth-related mRNAs showed reduced transcription but increased Nab3 binding, accompanied by downstream recruitment of Mtr4, and oligo(A) tailing. We conclude that transcription termination is followed by TRAMP-mediated RNA decay. Upregulated transcripts evaded increased surveillance factor binding following glucose withdrawal. Some upregulated genes showed use of alternative transcription starts to bypass strong NNS binding sites. We conclude that nuclear surveillance pathways regulate both positive and negative responses to glucose availability.